Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.21273/jashs.138.6.433
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Effect for Glycine on Root System Growth of Habanero Pepper

Abstract: Amino acids, a major fraction of the low-molecular-weight organic nitrogen in soil, act as signaling molecules that indicate the presence of nutrient-rich patches to the roots. To characterize the effects of amino acids on root growth, we used seedlings of habanero pepper (Capsicum chinense), one of the most widely cultivated annual spice crops in the world. We tested the effect of L-glutamate, L-aspartate, and glycine on the primary root of seedlings grown aseptically under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
(66 reference statements)
3
8
0
Order By: Relevance
“…One important finding of this study is that application of an ethylene biosynthesis inhibitor (0.5 or 1 μM AVG) or perception blocker (10 μM AgNO 3 ) to NaNO 3 + Gly-treated pak choi markedly alleviated the inhibition of primary root length under agar plate conditions ( Fig 5 and S5 Fig ). These findings are in agreement with Domínguez-May et al (2013), who suggested that ethylene played a regulatory role in the inhibitory effects of Gly in habanero pepper [ 24 ]. Moreover, we also showed that exogenous application of 0.5 μM AVG and 10 μM AgNO 3 could markedly increase the 15 NO 3 - -N uptake rate in hydroponically grown pak choi seedlings in response to NaNO 3 + Gly (Figs 6 and 7 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…One important finding of this study is that application of an ethylene biosynthesis inhibitor (0.5 or 1 μM AVG) or perception blocker (10 μM AgNO 3 ) to NaNO 3 + Gly-treated pak choi markedly alleviated the inhibition of primary root length under agar plate conditions ( Fig 5 and S5 Fig ). These findings are in agreement with Domínguez-May et al (2013), who suggested that ethylene played a regulatory role in the inhibitory effects of Gly in habanero pepper [ 24 ]. Moreover, we also showed that exogenous application of 0.5 μM AVG and 10 μM AgNO 3 could markedly increase the 15 NO 3 - -N uptake rate in hydroponically grown pak choi seedlings in response to NaNO 3 + Gly (Figs 6 and 7 ).…”
Section: Discussionsupporting
confidence: 92%
“…In both the agar plate and hydroponic systems, exogenous Gly significantly reduced primary root length ( Fig 1A, 1C and 1D , Fig 2A and S1 Fig ). This is similar to the effects of single amino acids, such as L -Glu and Gly [ 21 , 24 , 45 ] and mixtures of N sources supplied with NO 3 - -N and L -Glu [ 19 , 20 ] on plants grown on agar plates. Only Walch-Liu, Forde (2008) and Leblanc et al (2013) have investigated the effect of Glu on root development in the presence of both NO 3 - -N and Glu; the mixtures used in those studies more closely resemble soil conditions.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations